Penerapan Teknik Slow Deep Breathing pada Post Operasi Kolealitiasis dengan Masalah Keperawatan Nyeri Akut di Ruang ICU RSD Gunung Jati Kota Cirebon - Muhammad Fazril; Ahmad Syaripudin; Lily Wahyuni (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2026)
Background: Acute pain is a common problem experienced by patients after cholelithiasis surgery due to tissue injury and the inflammatory process resulting from surgical procedures. Uncontrolled pain can interfere with mobilization, rest, and the recovery process. Slow deep breathing is a non-pharmacological intervention that can help reduce pain by promoting relaxation and decreasing sympathetic nervous system activity. Objective: To determine the application of Evidence-Based Nursing through slow deep breathing techniques for acute pain management in post-cholelithiasis surgery patients. Methods: A case study was conducted on post-cholelithiasis surgery patients experiencing acute pain. Pain intensity was assessed using the Visual Analog Scale (VAS) before and after the implementation of slow deep breathing therapy for approximately 5–10 minutes. Data were collected through interviews, observations, physical examinations, and nursing documentation. Results: The implementation of slow deep breathing resulted in a reduction in pain intensity. Patients reported decreased pain levels, appeared more relaxed, showed reduced facial grimacing, and experienced improved comfort after the intervention. Implications: Slow deep breathing is effective in reducing acute pain in post-cholelithiasis surgery patients and can be applied as a complementary non-pharmacological nursing intervention in pain management.